Pre-master programs for foreign citizens - N. I. Guzarova; G. V. Kashkan; N. B. Shakhova (Высшее образование в России)
This paper considers actuality, scientific and methodological principles of the Pre-Master program design for foreign citizens, as well as educational technology for its realization. According to the analysis of the experience realization of the Pre-Bachelor and Pre-Master programs for foreign citizens in foreign and Russian universities, the differences betweenthese programs and the specific features of the Pre-Master programs are shown. The results of the initial monitoring of the Pre-Master program realization in Tomsk Polytechnic University are analyzed and proposals for its further development are presented.